Gamification and support to self-regulation as a means to promote practice sharing for teacher professional development (Ludificación y fomento de la autorregulación para incentivar el intercambio de prácticas docentes en el desarrollo profesional del profesorado). Issue 4 (2nd October 2022) - Passarelli, Marcello; Dagnino, Francesca-Maria; Persico, Donatella; Pozzi, Francesca; Manganello, Flavio
ABSTRACT: The most common form of teachers' professional development (TPD) — one-shot courses using formal, transmissive methodologies — often fails to prepare teachers for complex challenges or build a long-term community of teachers. Indeed, the role of practice-sharing in informal learning contexts, and specifically in teachers' communities of practice, is regarded as essential for effective TPD in the academic literature. In this paper we argue for the need to leverage gamification and self-regulated learning skills as ways for overcoming the barriers preventing teachers from engaging in practice-sharing. The paper includes a case study of a TPD pathway in which gamification and support to self-regulated learning are harnessed to bridge the gap between formal learning and informal practices in professional development. In our proposed approach, the formal component of TPD intends to ensure an evidence-based background to teachers' competence, while the informal component intends to draw on their teaching practice to complement it.